On offset-free Model Predictive Control with Long Short-Term Memory Networks. Issue 1 (2023) - Schimperna, I.; Toffanin, C.; Magni, L.
Abstract: This paper addresses offset-free reference tracking of asymptotically constant reference signals and disturbances using Model Predictive Control with a Long Short-Term Memory Network model. Basically, an error free output estimation and an error free nominal tracking for time-varying references are proposed for an Incremental Input-to-State Stable Long Short-Term Memory Network. This implies an offset-free Model Predictive Control algorithm.